2011 IEEE International Symposium on Biomedical Imaging: From Nano to Macro 2011
DOI: 10.1109/isbi.2011.5872766
|View full text |Cite
|
Sign up to set email alerts
|

Autism diagnostics by centerline-based shape analysis of the Corpus Callosum

Abstract: Autism severely impairs personal behavior and communication skills, so that improved diagnostic methods are called for. Neu ropathological studies have revealed abnormal anatomy of the Cor pus Callosum (CC) in autistic brains. We explore a possibility of distinguishing between autistic and normal (control) brains by quan titative CC shape analysis in the 3D maguetic resonance images (MRI). Our approach consists of the three steps: (i) segmenting the CC from a given 3D MRI using the learned CC shape and visual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…The mean classification accuracy using poses, shapes, and a combination of poses and shapes was 56%, 60%, and 64%, respectively, for an image Elnakib et al [47] obtained notably better classification accuracy, using a method shown in Figure 3.7, for autistic and control subjects by analyzing the corpus callosum centerline:…”
Section: Medial Axis and Skeletal Analysis Chapter 3 Survey Of Shapementioning
confidence: 98%
See 3 more Smart Citations
“…The mean classification accuracy using poses, shapes, and a combination of poses and shapes was 56%, 60%, and 64%, respectively, for an image Elnakib et al [47] obtained notably better classification accuracy, using a method shown in Figure 3.7, for autistic and control subjects by analyzing the corpus callosum centerline:…”
Section: Medial Axis and Skeletal Analysis Chapter 3 Survey Of Shapementioning
confidence: 98%
“…Egaas et al [45], Schumann et al [46], and Elnakib et al [47] all implicated the corpus callosum in the development of autism. The corpus callosum is the largest single fiber bundle in the brain, being responsible for connecting the two hemispheres of the brain.…”
Section: Neuropathology Of Autism Spectrum Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…An approach to extract the centerline of the 3D CC is presented based on solving Equation (13) [9,[194][195][196][269][270][271][272][273]. The main steps of the centerline extraction approach are detailed in Algorithm 9.…”
Section: Centerline Extraction From the CCmentioning
confidence: 99%